Efficacy and Safety of Intrapleural Fibrinolytic Therapy in Empyema Thoracis: A Meta-Analysis of Clinical Outcomes - Aldo Yulian; Oea Khairsyaf; Fenty Anggrainy (HM Publisher, 2025)
Background: Empyema thoracis is a severe pulmonary condition characterized by pus accumulation in the pleural space. Intrapleural fibrinolytic therapy is used adjunctively to break down loculations and facilitate lung re-expansion. This meta-analysis evaluated the efficacy and safety of this treatment in adults with empyema thoracis. Methods: A systematic search of PubMed, Embase, and Cochrane Central Register of Controlled Trials was conducted (January 2013 - December 2023) for randomized controlled trials (RCTs) comparing intrapleural fibrinolytics with placebo or no fibrinolytic therapy in adults with empyema. Primary outcomes were treatment success (radiographic improvement and/or clinical resolution), duration of hospital stay, and mortality. Secondary outcomes included major bleeding and bronchopleural fistula. Data were pooled using a random-effects model, and risk ratios (RR) or mean differences (MD) with 95% confidence intervals (CI) were calculated. Results: Six RCTs (n=623 patients) met the inclusion criteria. Intrapleural fibrinolytic therapy showed a significantly higher treatment success rate than the control (RR 1.42, 95% CI 1.18-1.72, p=0.001) and significantly reduced hospital stay (MD -2.84 days, 95% CI -3.36 to -2.33, p<0.001). No significant difference in mortality was found (RR 0.95, 95% CI 0.46-1.93, p=0.93). The incidence of major bleeding and bronchopleural fistula was similar between the groups. Conclusion: Intrapleural fibrinolytic therapy significantly improves treatment success and reduces hospital stays without increasing mortality or major complications. These findings support its use as an adjunctive therapy for drainage in managing empyema thoracis in adults.